Penerapan Kurikulum Merdeka Melalui Model Pembelajaran Project Based Learning (PjBL) dalam Pembuatan Tumpeng untuk Meningkatkan Kreativitas Siswa di Kelas X SMA Negeri 4 Surakarta - Rahmadhani, Fitria Suci; Suryani, Mareta Dwi; Astuti, Sri; Sabandi, Muhammad (Education Achievement: Journal of Science and Research, 2025)
The aim of the research is to determine the application of the Merdeka Curriculum through the Project Based Learning (PjBL) model in making tumpeng to increase student creativity in the production process material in class X SMA Negeri 4 Surakarta. The independent curriculum focuses on student-centered learning. This research uses a qualitative descriptive research type. Data collection techniques were carried out using observation, documentation and interviews. Data analysis uses qualitative descriptive analysis. The object of this research is student creativity in production process material in class X SMA Negeri 4 Surakarta for the 2024/2025 academic year with a total of 286 students. The results of this research show that the implementation of the Merdeka Curriculum through the Project Based Learning (PjBL) model increases student creativity through making tumpeng in the production process material in class X SMA Negeri 4 Surakarta.